A taxonomic mystery for more than 150 years: Identity, systematic position and Malagasy origin of the snake Elapotinus picteti Jan, 1862, and synonymy of Exallodontophis Cadle, 1999 (Serpentes: Lamprophiidae) - Kucharzewski, Christoph; Raselimanana, Achille P.; Wang, Cynthia; Glaw, Frank (Zootaxa, 2014)
Elapotinus picteti Jan, 1862 is an enigmatic snake taxon that has been described without locality data. Genus and species, both based on the unique holotype, were considered to belong to the venomous African Aparallactinae for more than a century, but although this taxon was never rediscovered it was accepted as a valid species until present. To clarify the taxonomic status of E. picteti its characters were compared with literature and determination keys for the whole world. This literature survey and the subsequent study of type specimens revealed that the monotypic Elapotinus is a subjective senior synonym of the monotypic Malagasy pseudoxyrhophiine snake genus Exallodontophis Cadle, 1999 which is characterized by its unique aglyphous dentition. We therefore transfer Elapotinus from the lamprophiid subfamily Aparallactinae to the subfamily Pseudoxyrhophiinae. Furthermore, Elapotinus picteti strongly resembles the Malagasy species Exallodontophis albignaci (Domergue, 1984) in external morphology, coloration and dentition. As a consequence we consider Elapotinus picteti a subjective senior synonym of Exallodontophis albignaci.